Not All Prosecutions are Created Equal: Less counting prosecutions, more making prosecutions count - McAdam, Marika (Anti-Trafficking Review, 2016)
Response to ATR Debate Proposition: ‘Prosecuting trafficking deflects attention from much more important responses and is anyway a waste of time and money’